INSAN KAMIL DALAM PEMIKIRAN MUHAMMAD NAFIS AL-BANJARI DAN ABDUSH-SHAMAD AL-FALIMBÂNÎ DALAM KITAB AD-DURR AN-NAFIS DAN SIYAR AS-SÂLIKÎN (SEBUAH STUDI PERBANDINGAN) - Rodiah, Rodiah (Jurnal Studia Insania, 2015)
This paper tries to explore the concept of Insan Kamil through two books of Sufism, ad-Durr an-Nafis by Muhammad Nafis al-Banjari and Siyar as-Salikin by Abdush-Shamad al-Falimbânî. The method used in this paper comparative descriptive approach, because the studies referred to in this study aims to look at the similarities and differences of the concept of Insan Kamil contained in both books. These results indicate that the thought of Muhammad Nafis al-Banjari in the book ad-Durr an-Nafis and Abdush-Samad al-Falimbânî in the book Siyar al-Salikin against the concept of Insan Kamil has the same basic concept, in addition to the typical thinking its own distinct between the two.